Staphylococcal disease in Africa: another neglected 'tropical' disease. (January 2013) - Herrmann, Mathias; Abdullah, Salim; Alabi, Abraham; Alonso, Pedro; Friedrich, Alexander W; Fuhr, Günther; Germann, Anja; Kern, Winfried V; Kremsner, Peter G; Mandomando, Inacio; Mellmann, Alexander C; Pluschke, Gerd; et al.
The term 'neglected tropical diseases' predominantly refers to single-entity, mostly parasitic diseases. However, a considerable morbidity and mortality burden is carried by patients infected with Gram-positive cocci and Gram-negative bacilli that are prevalent all over the world, yet have impact in tropical and developing countries, particularly in children, with much higher incidence rates than those reported from developed countries. Staphylococcus aureus is among these pathogens. The African–German StaphNet consortium uses microbiological characterization of African S. aureus isolates, including identification of virulence factors, alongside the gathering of epidemiological and clinical data in an innovative research network between a European country (Germany) and several African partners. By creating an accessible strain repository and by implementing personnel training and capacity building, this network aims to put staphylococcal disease on the international agenda as a truly neglected condition with a major global impact on public health.